Turkish teachers’ values with rational and non-rational truth and teacher emotions in teaching - Ünal, Kübra; Myyry, Liisa; Toom, Auli (Frontiers in Psychology, 2024)
The aim of this study was to clarify the relationships between personal values, truth-related values and emotions among Turkish teachers. The data were collected from 279 teachers with the Portrait Value Questionnaire (PVQ) where rational truth and non-rational truth values were added, and with the Teacher Emotions Scale (TES). This study used a cross-sectional correlational research design.The circular structure of the Schwartz Value Theory was tested by multidimensional scaling. The data analysis aimed to uncover relationships between personal values, truth-related values, and emotions. Rational truth emerged near self-direction and self-transcendence, yet items measuring non-rational truth were scattered among values. Females had higher regard for self-direction and hedonism than males. Non-rational truth was negatively correlated with enjoyment, while it was positively correlated with anxiety. The implications for gender roles in Turkish society are discussed.